Effect of tiotropium on neural respiratory drive during exercise in severe COPD. (February 2015) - Qin, Yin-Yin; Li, Rui-Fa; Wu, Guo-Feng; Zhu, Zheng; Liu, Jie; Zhou, Cheng-Zhi; Guan, Wei-Jie; Luo, Jia-Ying; Yu, Xin-Xin; Ou, Yang-Ming; Jiang, Mei; Zhong, Nan-Shan; et al.
Abstract: Background: Studies have shown that tiotropium once daily reduces lung hyperinflation and dyspnea during exercise and improves exercise tolerance in patients with COPD. Mechanisms underlying the effects of the muscarinic receptor antagonist tiotropium on COPD have not been fully understood. Objective: In this study, we investigated whether improvement in neural respiratory drive is responsible for reducing dyspnea during exercise and improving exercise tolerance in COPD. Methods: Twenty subjects with severe COPD were randomized into two groups: no treatment (Control, n = 10, 63.6 ± 4.6 years, FEV1 29.6 ± 13.3%pred) or inhaled tiotropium 18 μg once daily for 1 month ( n = 10, 66.5 ± 5.4 years, FEV1 33.0 ± 11.1%pred). All subjects were allowed to continue their daily medications other than anti-cholinergics during the study. Constant cycle exercise with 75% of maximal workload and spirometry were performed before and 1 month after treatment. Diaphragmatic EMG (EMGdi) and respiratory pressures were recorded with multifunctional esophageal catheter. Efficiency of neural respiratory drive, defined as the ratio of minute ventilation (VE) and diaphragmatic EMG (VE/EMGdi%max), was calculated. Modified British Medical Research Council Dyspnea Scale (mMRC) was used for the evaluation of dyspnea before and after treatment. Results: There was no significant difference in spirometry before and after treatment in both groups. Diaphragmatic EMG decreased significantly at rest (28.1 ± 10.9% vs. 22.6 ± 10.7%, P < 0.05) and mean efficiency of neural respiratory drive at the later stage of exercise increased (39.8 ± 2.9 vs. 45.2 ± 3.9, P < 0.01) after 1-month treatment with tiotropium. There were no remarkable changes in resting EMGdi and mean efficiency of neural respiratory drive post-treatment in control group. The score of mMRC decreased significantly (2.5 ± 0.5 vs. 1.9 ± 0.7, P < 0.05) after 1-month treatment with tiotropium, but without significantly difference in control group. Conclusion: Tiotropium significantly reduces neural respiratory drive at rest and improves the efficiency of neural respiratory drive during exercise, which might account for the improvement in exercise tolerance in COPD.